Acquired Hemophilia in Female - A Case Report - Karmaker, Madhabi; Zerin, Israt; Afrose, Salma; Rahman, Md Mujibur; Azad, Khan Abul Kalam (Journal of Medicine, 2017)
Acquired hemophilia is a rare but acquired bleeding diathesis caused by autoimmune depletion of Factor VIII or IX. Diagnosis of Acquired Hemophilia requires clinical acumen. The condition is often under diagnosed as because it is rare and patients usually dont have any unusual personal or family history of bleeding episodes. Acquired hemophilia has an equal sex distribution. So, clinicians should suspect acquired hemophilia in any patients with unexplained persistent and profound bleeding from uncommon soft tissues and mucosa and having prolonged activated partial thromboplastin time (APTT) without other causes. Here we will report a 50-year-old lady presenting with recurrent spontaneous bruises and joint pain and swelling for 2 years. On examination we found multiple bruises and ecchymosis of different sizes with varying colour changes from bluish to greenish over different parts of her body including face, right shoulder, right elbow joint and 2nd and 3rd PIP joints. Lab findings showed decreased Hemoglobin with prolonged APTT which didnt correct in mixing study. After exclusion of other possible pathological conditions and on the basis of lab criteria we diagnosed the case as Acquired Hemophilia. She was successfully treated with blood transfusion, recombinant activated factor VIII, Steroid and supportive treatments and was discharged with improving symptoms, stable hematocrit and resolving bruises. J MEDICINE July 2017; 18 (2) : 119-122